2004
DOI: 10.1099/ijs.0.03007-0
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella profunda sp. nov., isolated from deep marine sediment of the Nankai Trough

Abstract: A novel piezotolerant, mesophilic, facultatively anaerobic, organotrophic, polarly flagellated bacterium (strain LT13a(T)) was isolated from a deep sediment layer in the Nankai Trough (Leg 190, Ocean Drilling Program) off the coast of Japan. This organism used a wide range of organic substrates as sole carbon and energy sources: pyruvate, glutamate, succinate, fumarate, lactate, citrate, peptone and tryptone. Oxygen, nitrate, fumarate, ferric iron and cystine were used as electron acceptors. Maximal growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 43 publications
4
40
1
Order By: Relevance
“…S3). The presence of phosphatidylethanolamine and phophatidylglycerol was consistent with analyses of other species of the genus Shewanella (Toffin et al, 2004;Kim et al, 2012;Park & Jeon, 2013).…”
Section: Cells Of Strain St-6supporting
confidence: 84%
See 1 more Smart Citation
“…S3). The presence of phosphatidylethanolamine and phophatidylglycerol was consistent with analyses of other species of the genus Shewanella (Toffin et al, 2004;Kim et al, 2012;Park & Jeon, 2013).…”
Section: Cells Of Strain St-6supporting
confidence: 84%
“…Members of the genus Shewanella are widely distributed in marine environments including seawater (Makemson et al, 1997;Brettar et al, 2002;Park et al, 2009;Sung et al, 2012), sediment (Venkateswaran et al, 1999;Toffin et al, 2004;Gao et al, 2006;Chang et al, 2008;Pankaj et al, 2011;Kim et al, 2012;Yoon et al, 2012), tidal flats (Yoon et al, 2004Park & Jeon, 2013), marine invertebrates (Ivanova et al, 2004b;Lee et al, 2006;Yang et al, 2006) and fish (Satomi et al, 2006(Satomi et al, , 2007, and Antarctic sea ice (Bowman et al, 1997;Bozal et al, 2002Bozal et al, , 2009, and some species are found in activated sludge (Xu et al, 2005) and clinical samples (Brink et al, 1995;Debois et al, 1975;Holmes et al, 1975;Nozue et al, 1992).…”
mentioning
confidence: 99%
“…Table 1. Differential characteristics of strains A3F-7 T and ssthio04PA2-7c (Paramoritella gen. nov.) and related genera Data for reference genera were taken from the following studies: Urakawa et al (1998), Nogi et al (1998b), Nogi & Kato (1999), Benediktsdó ttir et al (2000), Lunder et al (2000), Xu et al (2003) and Kim et al (2008) (Moritella); Bowman et al (1997), Bowman (2005), Nogi et al (1998a), Venkateswaran et al (1999), Leonardo et al (1999), Ivanova et al (2001Ivanova et al ( , 2003Ivanova et al ( , 2004a, Bozal et al (2002), Skerratt et al (2002), Brettar et al (2002, Satomi et al (2003Satomi et al ( , 2006Satomi et al ( , 2007, Yoon et al (2004a, b), Toffin et al (2004), Xu et al (2005), Zhao et al (2005Zhao et al ( , 2006Zhao et al ( , 2007 …”
Section: Description Of Paramoritella Alkaliphila Sp Novmentioning
confidence: 99%
“…At the time of writing, the genus Shewanella comprised 45 recognized species (http://www.bacterio.-cict.fr/s/shewanella.html). Strains of the genus Shewanella have been isolated from a variety of sources including marine environments (Venkateswaran et al, 1998;Nealson et al, 1991;Nogi et al, 1998;Ivanova et al, 2001Ivanova et al, , 2004aBozal et al, 2002;Skerratt et al, 2002;Yoon et al, 2004b;Gram et al, 1987;Stenstrom & Molin, 1990;Gram & Huss, 1996;Satomi et al, 2006Satomi et al, , 2007Lee et al, 2006;Satomi et al, 2003;Simidu et al, 1990;Yang et al, 2006), sediments (Myers & Nealson, 1988;Venkateswaran et al, 1999;Toffin et al, 2004;Yoon et al, 2004a;Gao et al, 2006;Zhao et al, 2005Zhao et al, , 2006Miyazaki et al, 2006;Xiao et al, 2007;Yang et al, 2007), clinical samples (Brink et al, 1995;Nozue et al, 1992;Levin, 1972;Debois et al, 1975;Holmes et al, 1975), oilfield fluids (Semple & Westlake, 1987) and activated sludge (Xu et al, 2005). They have also been implicated as opportunistic pathogens of humans and aquatic animals (Aguirre et al, 1994;Brink et al, 1995) and as the causal agents of proteinaceous food spoilage (Jorgensen & Huß, 1989).…”
mentioning
confidence: 99%